Highly skilled asylum seekers: Case studies of refugee students at a Swiss university - Sontag, Katrin (Migration Letters, 2018)
The article argues that the applicability and value of “skills” depend to a considerable degree on the way in which a person enters a country. Based on a study on potential university students with refugee backgrounds, it shows how difficult it can be to transfer skills through the migration channel of asylum in Switzerland and how social and cultural capital may be reduced. The space in which asylum seekers live and operate is restricted in such intersecting fields as mobility, time, finances, languages, or access to information. In addition, the educational system has regulations regarding recognition. The article raises questions as to how education systems in the destination countries recognize, integrate and develop skills. It makes the case for re-assessing the very term “highly skilled”, along with the notions and associations that surround it, as an empirical object of research, rather than accepting it as a category in its own right.